The cardiovascular risk profile of middle‐aged women with polycystic ovary syndrome. (24th November 2019) - Meun, Cindy; Gunning, Marlise N; Louwers, Yvonne V; Peters, Henrike; Roos‐Hesselink, Jolien; Roeters van Lennep, Jeanine; Rueda Ochoa, Oscar‐Leonel; Appelman, Yolande; Lambalk, Nils; Boersma, Eric; Kavousi, Maryam; Fauser, Bart CJM; et al.
Abstract: Objectives: Contradictory results have been reported regarding the association between polycystic ovary syndrome (PCOS) and cardiovascular disease (CVD). We assessed the cardiometabolic phenotype and prevalence of CVD in middle‐aged women with PCOS, compared with age‐matched controls from the general population, and estimated 10‐year CVD risk and cardiovascular health score. Design: A cross‐sectional study. Participants: 200 women aged >45 with PCOS, and 200 age‐matched controls. Measurements: Anthropometrics, insulin, lipid levels, prevalence of metabolic syndrome and type II diabetes. Ten‐year Framingham risk score and the cardiovascular health score were calculated, and carotid intima‐media thickness (cIMT) was measured. Results: Mean age was 50.5 years (SD = 5.5) in women with PCOS and 51.0 years (SD = 5.2) in controls. Increased waist circumference, body mass index and hypertension were more often observed in women with PCOS ( P < .001). In women with PCOS, the prevalence of type II diabetes and metabolic syndrome was not significantly increased and lipid levels were not different from controls. cIMT was lower in women with PCOS ( P < .001). Calculated cardiovascular health and 10‐year CVD risk were similar in women with PCOS and controls. Conclusions: Middle‐aged women with PCOS exhibit only a moderately unfavourable cardiometabolic profile compared to age‐matched controls, even though they present with an increased BMI and waist circumference. Furthermore, we found no evidence for increased (10‐year) CVD risk or more severe atherosclerosis compared with controls from the general population. Long‐term follow‐up of women with PCOS is necessary to provide a definitive answer concerning long‐term risk for CVD.